Data-fusion of high resolution X-ray CT, SEM and EDS for 3D and pseudo-3D chemical and structural characterization of sandstone. (July 2015) - De Boever, Wesley; Derluyn, Hannelore; Van Loo, Denis; Van Hoorebeke, Luc; Cnudde, Veerle
Highlights: We describe a workflow for multi-scale 3D analysis of rock samples. Using X-ray computed tomography and SEM-EDS, structure and composition is analyzed. Image registration is used to combine the different 2D and 3D methods. The method enables users to know the exact 3D location of subsamples. A combination of CT and SEM ads an extra dimension to compositional EDS maps. Abstract: When dealing with the characterization of the structure and composition of natural stones, problems of representativeness and choice of analysis technique almost always occur. Since feature-sizes are typically spread over the nanometer to centimeter range, there is never one single technique that allows a rapid and complete characterization. Over the last few decades, high resolution X-ray CT (μ-CT) has become an invaluable tool for the 3D characterization of many materials, including natural stones. This technique has many important advantages, but there are also some limitations, including a tradeoff between resolution and sample size and a lack of chemical information. For geologists, this chemical information is of importance for the determination of minerals inside samples. We suggest a workflow for the complete chemical and structural characterization of a representative volume of a heterogeneous geological material. This workflow consists of combining information derived from CT scans at different spatial resolutions with information from scanning electron microscopy and energy-dispersive X-ray spectroscopy.